2017
DOI: 10.1186/s12971-017-0139-6
|View full text |Cite
|
Sign up to set email alerts
|

Smoking and secondhand smoke exposure and prevalence of depressive symptoms during pregnancy in Japan: baseline data from the Kyushu Okinawa Maternal and Child Health Study

Abstract: BackgroundEpidemiological evidence on the relationship between smoking and secondhand smoke (SHS) exposure and depressive symptoms during pregnancy has been limited. The present cross-sectional study examined this issue in Japan.MethodsBetween April 2007 and March 2008, 1757 pregnant women who lived in one of seven prefectures on Kyushu Island in southern Japan or in Okinawa Prefecture, an island chain in the southwest of Japan, participated in the Kyushu Okinawa Maternal and Child Health Study, a prebirth coh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…The adverse health effect of cigarette smoke on the fetus includes, an increased risk of strabismus in the offspring [71], clubfoot [72], low birth weight for gestational age (LBWGA), low birth weight, preterm births (28,29), increased odds of elevated levels of antisocial behaviors during adolescence and adulthood, as well as violent and nonviolent outcomes [73], an increased risk of wheeze in children [74], and almost 3 times increased risk of congenital heart defects [75]. Moreover, tobacco smoke during pregnancy increases the prevalence of depressive symptoms during pregnancy [76]. This indicated the need of tobacco smoking intervention at home, work and public places to improve fetal, maternal and societal health.…”
Section: Plos Onementioning
confidence: 99%
“…The adverse health effect of cigarette smoke on the fetus includes, an increased risk of strabismus in the offspring [71], clubfoot [72], low birth weight for gestational age (LBWGA), low birth weight, preterm births (28,29), increased odds of elevated levels of antisocial behaviors during adolescence and adulthood, as well as violent and nonviolent outcomes [73], an increased risk of wheeze in children [74], and almost 3 times increased risk of congenital heart defects [75]. Moreover, tobacco smoke during pregnancy increases the prevalence of depressive symptoms during pregnancy [76]. This indicated the need of tobacco smoking intervention at home, work and public places to improve fetal, maternal and societal health.…”
Section: Plos Onementioning
confidence: 99%
“…Smoke of the cigarette has both maternal and neonatal adverse effects. The adverse maternal effects include maternal depression during pregnancy [33] while the fetal effects include an increased risk of strabismus in the offspring [34], clubfoot [35], low birth weight and preterm births [36]. Furthermore, during adolescence and adulthood, antisocial behaviors [37], increased risk of wheezing in children [38] and risk of congenital heart defects can be ensued [39].…”
Section: Introductionmentioning
confidence: 99%
“…The literature search and study selection process were shown in Figure 1. After excluding studies that did not meet the inclusion criteria, 24 studies were included in the present meta-analysis [7,8,9,10,20,21,22,23,24,25,26,27,28,29,30,31,32,33,34,35,36,37,38,39], including 22 cross-sectional studies and two cohort studies. All the study participants were from the healthy population, rather than the clinical population.…”
Section: Resultsmentioning
confidence: 99%